2017
DOI: 10.1177/0269216317735246
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care in patients with haematological neoplasms: An integrative systematic review

Abstract: Despite a growing interest in palliative care for haematological malignancies patients, the evidence base needs to be strengthened to expand our knowledge about palliative care in this patient group. The results of this review support the need to develop closer cooperation and communication between the palliative care and onco-haematology departments to improve patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 124 publications
2
49
1
2
Order By: Relevance
“…Various studies indicate that the mean number of physical symptoms, symptom burden, and level of distress in HM patients are at least as high as in patients with advanced solid tumors [2,3]. Their performance status often seems to be even worse [4].…”
Section: Problems and Needs Of Patients With Advanced Hematological Mmentioning
confidence: 99%
See 3 more Smart Citations
“…Various studies indicate that the mean number of physical symptoms, symptom burden, and level of distress in HM patients are at least as high as in patients with advanced solid tumors [2,3]. Their performance status often seems to be even worse [4].…”
Section: Problems and Needs Of Patients With Advanced Hematological Mmentioning
confidence: 99%
“…A review analysis even demonstrated that they also have a more than 50% reduced chance to receive specialist palliative or hospice care compared to solid cancers patients [10]. In patients in whom palliative or hospice care is initiated, they are often limited to the end-of-life phase with late referral to palliative care [3]. Patients with HM are more likely to die within 24 hours after hospice enrollment or within 7 days after hospice admission compared to solid tumor patients [4].…”
Section: End-of-life Care In Patients With Hematological Malignanciesmentioning
confidence: 99%
See 2 more Smart Citations
“…A significant body of international literature highlights there are challenges providing palliative and end-of-life care in the specialty area of clinical malignant haematology (Moreno-Alonso et al, 2017). People with a haematological malignancy often experience a fluctuating and unpredictable illness trajectory and can deteriorate rapidly to a terminal event (Hung et al, 2013;Manitta, Philip, & Cole-Sinclair, 2010;McGrath & Holewa, 2007).…”
Section: Introductionmentioning
confidence: 99%